2015
DOI: 10.1177/0194599815598969
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Langerhans Cell Histiocytosis Bone Lesion in Pediatric Patients

Abstract: Due to its rarity and variability in presentation and severity, treatment of these lesions has yet to be standardized. Based on the review, a diagnosis and treatment algorithm was created for head and neck surgeons when encountering these types of lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 63 publications
0
39
0
1
Order By: Relevance
“…Two of them had multiple cranial bone lesions involving middle ear, mastoids. It has been reported that patients with multisystem disease and craniofacial bone involvement at diagnosis carry a significantly increased risk of developing DI during their course 22,26 . Among patients with LCH, approximately 25% of them may be diagnosed with pituitary involvement within 5-10 years of follow-up 20,23 .…”
Section: Multisystem Lch (Ms-lch) (N:11)mentioning
confidence: 99%
See 1 more Smart Citation
“…Two of them had multiple cranial bone lesions involving middle ear, mastoids. It has been reported that patients with multisystem disease and craniofacial bone involvement at diagnosis carry a significantly increased risk of developing DI during their course 22,26 . Among patients with LCH, approximately 25% of them may be diagnosed with pituitary involvement within 5-10 years of follow-up 20,23 .…”
Section: Multisystem Lch (Ms-lch) (N:11)mentioning
confidence: 99%
“…In children, common sites of bone involvement include craniofacial bones, femur, ribs, vertebra, and humerus. Craniofacial bone lesions of LCH are considered as CNSrisk lesions 26 . Bone involvement was present in 70% (n:14) of our patients.…”
Section: Multisystem Lch (Ms-lch) (N:11)mentioning
confidence: 99%
“…En los pacientes con afectación ósea el tratamiento de elección es el legrado o la escisión quirúrgica, siempre que la localización lo permita. A veces es necesario sumar radioterapia, glucocorticoides intralesionales, quimioterapia o combinaciones terapéuticas, con buen pronóstico 6 .…”
Section: Histiocitosis Mandibular De Células De Langerhansunclassified
“…The distinctive cells involved in LCH are bone marrow-derived histiocytes, which are activated dendritic cells and macrophages resembling Langerhans cells in morphology and immunophenotype. Aggregation of eosinophilic leucocytes can also be present 1 2…”
Section: Introductionmentioning
confidence: 99%